Miracula, saints' cults and socio-political landscapes: Bobbio, Conques and post-Carolingian society - Taylor, Faye C. (2012)
Despite the centrality of monastic sources to debates about social and political transformation in post-Carolingian Europe, few studies have approached the political and economic status of monasteries and their saints' cults in this context, to which this thesis offers a comparative approach. Hagiography provides an interesting point of analysis with respect to the proposition of mutation féodale, and more importantly to that of the mutation documentaire and its relation to monastic 'reform', which Part I discusses.